Degradation of glycosphingolipids in oyster: ceramide glycanase and ceramidase in the hepatopancreas of oyster, Crassostrea virginica - Pavlova, Nadejda V.; Li, Su-Chen; Li, Yu-Teh (Glycoconjugate journal, 2018)
The hepatopancreas of oyster, Crassostrea virginica , was found to contain two unique glycosphingolipid (GSL) cleaving enzymes, ceramide glycanase (CGase) and ceramidase. These two enzymes were found to be tightly associated together through the consecutive purification steps including gel filtration, hydrophobic interaction and cation-exchange chromatographies. They were separated only by preparatory SDS-PAGE. The purified CGase was found to have a molecular mass of 52 kDa and pH optimum of 3.2–3.3. This enzyme prefers to hydrolyze the acidic GSLs, II 3 SO 3 LacCer and gangliosides over the neutral GSLs. Oyster ceramidase was found to have a molecular mass of 88 kDa and pH optimum of 4–4.5. Since oyster ceramidase greatly prefers ceramides with C 6 to C 8 fatty acids, C 6 -ceramide ( N -hexanoyl-D-sphingosine) was used as the substrate for its purification and characterization. The oyster acid ceramidase also catalyzed the synthesis of ceramide from a sphingosine and a fatty acid. For the synthesis, C 16 and C 18 fatty acids were the best precursors. The amino acid sequences of the two cyanogenbromide peptides derived from the purified ceramidase were found to have similarities to those of several neutral and alkaline ceramidases reported. The tight association of CGase and ceramidase may indicate that CGase in oyster hepatopancreas acts as a vehicle to release ceramide from GSLs for subsequent generation of sphingosines and fatty acids by ceramidase to serve as signaling factors and energy source.